Pathologies of oral and sinonasal mucosa following facial vascularized composite allotransplantation - Kauke-Navarro, Martin; Tchiloemba, Bianief; Haug, Valentin; Kollar, Branislav; Diehm, Yannick; Safi, Ali-Farid; Treister, Nathaniel S.; Annino, Donald J.; Marty, Francisco M.; Lian, Christine G.; Murphy, George F.; Pomahac, Bohdan (Journal of plastic, reconstructive & aesthetic surgery, 2021)
Background - Cutaneous changes of facial vascularized composite allotransplants (fVCAs) are extensively described in the literature. Parts of the nose, nasal, and oral cavities are included in most fVCAs. Distinctively, the nose and mouth are lined by mucosa. Little is known about the histopathology and complications of the mucosa involved in fVCA patients. - Methods - The study constitutes a retrospective cohort study of nine fVCA patients. Medical records were reviewed for information about changes of oral and nasal mucous membranes. Types of mucosal lesions were recorded and analyzed. Uni- and multivariate generalized estimating equation (GEE) models were used to assess the odds of developing mucosal inflammation in the presence of clinico-pathologic variables. - Results - A total of 186 clinical encounters with examination of oral and nasal mucous membranes were included. Membranes were devoid of clinical pathology in 101 instances (53% of all clinical assessments). Ulcerations/erosions (27%), edema (18%), and erythema (14%) were the most common lesions. Oral lesions affected the lips (58%), buccal mucosa (38%), and palate (5%). Sinonasal processes predominantly affected nasal vestibules and septae. In univariate analysis, sirolimus, skin rejection, and skin Banff grade were associated with the presence of an acute inflammatory mucosal lesion (p<0.05). In multivariate analysis, skin Banff grade and sirolimus were independent predictors of mucosal inflammation. - Conclusion - Pathologies of fVCA mucous membranes are more common than previously reported. Mucosal assessment plays an important role in the pleomorphic allograft rejection process evaluation rather than diagnosis and treatment based on cutaneous pathology. A closer look at the pathophysiology of fVCA mucosal rejection and inflammation is warranted.